Sustainable Development Of The Coastal Towns In Southern Campania Region - Carlo Tesauro; Ferdinando Iannuzzi; Salvatore Patrizio (European Regional Science Association (ERSA), 2013)
The planning and management of territory has undergone profound changes in recent decades, mainly due to the renewed focus on the component of 'natural capital', which resulted in frequent legislative measures, including the establishment of new protected areas (both in ground and marine contexts), the evolution of the concept of sustainable development, up to the current approaches to territorial marketing and branding. The main problem arising from the sum of many innovations is to avoid any possible conflict, between them, that can reduce or cancel the positive effects. In particular, methods and strategies for a possible development must be compatible with both the extreme delicacy and fragility of the ecosystem in which they operate than with the legislation on protection of the environment of the park authorities. An emblematic example of this delicate balance can be found by the Cilento coast, the southern part of Campania region, included in the range that runs from Punta Licosa in Punta Infreschi, area that falls within the boundaries of the ?Cilento and Vallo di Diano? National Park and between the two Marine Parks of Costa Infreschi e Masseta and Santa Maria di Castellabate. This area, which features unique in many ways, was chosen to study not only the physical aspects (area's topography, geology, etc..), joined with flora and fauna, but also of the most exquisitely anthropic elements (the first permanent settlements - flowering already in pre Hellenistic age, historical development, urban planning and economic development of the territory itself) with the main intent to propose hypothesis for a possible socio-economic development aimed at promoting cultural, economic and social the territories administered for all the 9 municipalities (Ascea, Camerota, Casalvelino, Castellabate, Centola, Montecorice, Pisciotta, Pollica, San Mauro al Cilento) included in the area of study. References Calafati A.G. (2004): ?Conservazione e sviluppo locale?. Rivista geografica italiana. n. 1, pp.24. Carobene L., Brambati A. (1975): ?Metodo per l?analisi morfologica quantitativa delle spiagge?. Boll. Soc. Geol. It. 94, 479-493. Kingsford M.J., Battershill C.N. (1998): ?Studying temperate marine environments: A handbook for ecologists. University of Canterbury Press, Christchurch, pp. 344. Lee Z., Carter L.K., Mobley C.D., Steward R.G., Patch J.S. (1999): ?Hyperspectral remote sensing for shallow waters: Deriving bottom depths and water properties by optimizzation?. Applied optics, v.38, n. 18, p. 3831. Peano A. (2002): ?La politica del territorio alla svolta della sostenibilità?. Scienze Regionali, vol. 2, n. 1, pp. 7. Piazzi L., Balata D., Cinelli F.: (2002): ?Epiphytic macroalgal assemblages of Posidonia oceanica rhizomes in weatern Mediterranean?. Eur. J. Phycol. 37, 69-76. Sunamura T. (1992): ?Geomorphology of rocky coasts?. John Wiley & sons, pp.293.
Keywords: 330; Sustainable development; Mediterranean; coast; natural parks